Normally we charge $2.00 for this answer

Today, you can get it FOR FREE if you

g+1, Follow or Like, us

Show me how to post my homework

Just do my homework!

  • HTML tags will be transformed to conform to HTML standards.
  • Add rel="nofollow" to external links
Question
Submitted by edwin_laura96 on Mon, 2012-03-12 20:58
due on Fri, 2012-03-16 21:02
answered 3 time(s)
edwin_laura96 is willing to pay $5.00
edwin_laura96 bought 0 out of 1 answered question(s)

what is the solution to the system of equation? -7x+4y=6 -7x-y=-19

what is the solution to the system of equation? -7x+4y=6 -7x-y=-19

Answer
Submitted by mainakmajumder on Tue, 2012-03-13 02:21
teacher rated one time
3
price: $2.00

here is your answer(solution with graph)

body preview (42 words)

xxxxxxxxxxxxxxx
-7x-y=-19 xxxxxx

subtracting xxx equation ..(i) from equation ..(ii) we xxxx
xxxxxxxxxxxxxxxxxxxx
=>-7x-y+7x-4y=-25
=>-5y=-25
=>5y=25
=>y=25/5
xxxxx

xxxxxxx y=5 in xxx xxxxxxxx xxxxxxx xx xxxx

-7x-5=-19
xxxxxxxxxxx
xxxxxxxxx
xxxxxxx
xxxxxxxx
xxxxx

file1.jpg preview (0 words)


Buy this answer

Try it before you buy it
Check plagiarism for $2.00

Answer
Submitted by Doctor on Tue, 2012-03-13 09:56
teacher rated 0 times
0
price: $1.00

Step-by-Step Solution. (Including an attached plot.)

body preview (132 words)

xxx us xxxxxxxxx x xxxxxx

-7 x x x x = 6
xx x - y = - 19 multiply xxxx xxxxxxxx with xxxx
xxxxxxxxxxxxxxxxxx
-7 x x 4 y = x
x x + y x xx add both xxxxxxxxx
==================
x x x 5 x = 25 xxxxxx both sides xx xxx equation by x
y x 25/5 x 5

xxxx for x we xxxx xx e.g. xxx xxxxxx xxxxxxxx and solve it for xx

xx x x x x - 19 add y xx both xxxxx xx the equation
==================
-7 x = - 19 x y xxxxxx both sides xx xxx equation xx -7
x = (- 19 x y)/(-7) x xxx x xxxx

xxxxxxxx y=5:
x x (19 - xxxx = (19 - 5)/7 = xxxx = 2

xxxxxxxxx xxxx solution is:

x x xx x = xx

xxxx at xxx diagram attached. At x = 2 xxx x x x xxxx lines xxxxxxxxxx

file1.jpg preview (0 words)


Buy this answer

Try it before you buy it
Check plagiarism for $2.00

Answer
Submitted by Andrein on Mon, 2012-03-12 21:25
teacher rated 2 times
3
price: $1.00

Complete answer with step-by-step instructions

body preview (223 words)

The equation xxxx
-7 x x + 4 * x x 6
xx x x x y = xxx
We xxxxxxxx xxx second xxxxxxxx xxxx the xxxxx one xxx xx have:
-7 * x - xxxx * x x x * x x (-y) = x x xxxxx =
-7 x x + 7 * x x 4 * x x x x x + xx xx
x
xx xxxxxx out the common factor x from xxx xxxxx two xxxxx and xxx xxxxxx factor y

- - - more text follows - - -



Buy this answer

Try it before you buy it
Check plagiarism for $2.00